Are systematic review and guideline development tools useful? A Guidelines International Network survey of user preferences. Issue 3 (1st September 2020) - Munn, Zachary; Brandt, Linn; Kuijpers, Ton; Whittington, Craig; Wiles, Louise; Karge, Torsten
Abstract : Supplemental Digital Content is available in the text ABSTRACT: Background: There are now over 140 tools/programs that can assist in developing systematic reviews or clinical practice guidelines (CPGs). It is currently unclear which tools are used by systematic reviewers and CPG developers, which development processes they are used for, and what facilitators or barriers to their use exist. Methods: To determine which tools are currently being used by systematic reviewers and CPG developers, an online survey was administered during July–August 2017. Guidelines International Network individual and organizational members were invited to participate. Survey questions focused on the nature and frequency of members' use of tools to support systematic review and CPG development. Results: The overall response rate was 34%. The largest number of respondents developed one to five guidelines a year (48%). GRADEpro GDT was the most popular tool (26% of respondents) followed by Dropbox (16%) and RevMan (14%). From the options provided, the reason most respondents (85%) used particular tools was 'to be more efficient'. Most users stated they would use the tool again (95%), and 95% would recommend it to other organizations. However, respondents reported that tool efficiency and facilitators such as data sharing functionality were offset by their availability and cost, issues with structured data fields (that did not allow customization), and other technical and usability factors (e.g., features, workflows). Conclusion: The results of this survey provide a focus for discussing improvements in tools to meet the needs of systematic reviewers and CPG developers, and a basis from which to test the efficacy and appropriateness of various tools and platforms across a number of purposes and contexts.